Penyuluhan Dampak dan Konsekuensi Hukum Judi Online dalam Kalangan Remaja di SMK Taruna Bhakti Depok - Putri, Adinda Alvita; Ariono, Sujud; Hia, Baliterofi; eKO, Dedin Rohmat; Santoso, Santoso; Sutrisno, Andri (CV. Era Digital Nusantara, 2024)
Real Work Lectures (KKN) are an integral program in higher education to apply knowledge to society. IBLAM students, supported by Garuda Food and expert sources, held a legal outreach activity with the theme